Natural orifice transluminal endoscopic surgery in urology: The Chinese experience - Xiaofeng Zou; Guoxi Zhang; Tianpeng Xie; Yuanhu Yuan; Rihai Xiao; Gengqing Wu; Xiaoning Wang; Hui Xu; Folin Liu; Yuting Wu; Yunfeng Liao; Quanliang Liu; et al. (Asian Journal of Urology)
Objective: To describe the Chinese experience of natural orifice transluminal endoscopic surgery (NOTES) in urology. Methods: From December 2008 to May 2017, 35 animal experiments and 305 clinical surgeries of NOTES or natural orifices specimen extractions (NOSE) were performed in China. The animal experiments included five kidney biopsies, 24 nephrectomies and six partial nephrectomies. The clinical surgeries included 12 transvaginal NOSE (TV-NOSE), 266 hybrid transvaginal NOTES (TV-NOTES) and 27 pure TV-NOTES. The TV-NOSE procedure was performed in five transumbilical laparoendoscopic single-site (U-LESS) nephrectomies, four suprapubic-assisted laparoendoscopic single-site surgery (SA-LESS) nephroureterectomies, and three laparoscopic radical cystectomies. The hybrid TV-NOTES procedure included 210 nephrectomies, 31 adrenalectomies, eight nephroureterectomies, 13 partial nephrectomies, and four heminephrectomies. The pure TV-NOTES procedure included five renal cyst decortications and 22 nephrectomies. Results: A total of 29 animal experiments were successfully performed. One partial nephrectomy was converted to standard laparoscopic surgery. Two kidney biopsies and two nephrectomies were unsuccessful. A total of 297 clinical surgeries were successfully performed. Six patients who underwent hybrid TV-NOTES were converted to open surgery. Two patients who underwent pure TV-NOTES were converted to SA-LESS. There were 22 major complications, 16 occurred intraoperatively and six postoperatively. The mean visual analog score (VAS) of 48 h after the operation was 2.5 points in TV-NOSE, 2.3 points in hybrid TV-NOTES and 1.7 points in pure TV-NOTES. The mean follow-up of 50.6 (3.0–87.0) months showed that all patients were in good condition. The umbilicus scars were nearly invisible in TV-NOSE and hybrid TV-NOTES. The vaginal incision healed well. Conclusions: TV-NOSE and TV-NOTES are feasible, safe, and effective with little injury, low pain, fast recovery, and good cosmetic outcomes in properly selected patients. They are worth consideration for urological clinical practice. Keywords: Minimally invasive surgery, Laparoscopy, Natural orifice transluminal endoscopic surgery, Transvaginal surgery, Urology, Chinese experience